Pengaruh Aplikasi Wordwall Dalam Pembelajaran Kosakata Bahasa Jepang Kelas XI SMK Nasional Padang - Putri, Ersi Rahma; Wikarya, Rahmi Oktayory (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2024)
The quantity and quality of an individual's vocabulary can be seen in their language proficiency. However, many students face difficulties in this aspect. Based on observations during the Education Field Practice at SMK Nasional Padang and interviews with subject teachers, one of the constraints for students in mastering vocabulary is the lack of interest and motivation. Therefore, the researcher aims to provide lessons with the aid of media to cultivate students' motivation in learning the Japanese language, particularly Japanese vocabulary (goi). The aim of this research is to determine the influence of the wordwall application on the acquisition of the Japanese language learning 11th-grade students at SMK Nasional Padang. The samples are 17 students and the study is classified as a quantitative research with pre-experimental one-group pretest-postest design and. In the hypothesis testing results, it was found that the paired sample t-test yielded a value of 0.000 < 0.05 and 7.727 > 2.131 or tcount > ttable. Consequently, it can be concluded the wordwall application has impact on the learning of Japanese vocabulary (goi) for 11th grade students at SMK Nasional Padang.